2006
DOI: 10.1152/japplphysiol.00464.2006
|View full text |Cite|
|
Sign up to set email alerts
|

Restrained whole body plethysmography for measure of strain-specific and allergen-induced airway responsiveness in conscious mice

Abstract: The mouse is the most extensively studied animal species in respiratory research, yet the technologies available to assess airway function in conscious mice are not universally accepted. We hypothesized that whole body plethysmography employing noninvasive restraint (RWBP) could be used to quantify specific airway resistance (sRaw-RWBP) and airway responsiveness in conscious mice. Methacholine responses were compared using sRaw-RWBP vs. airway resistance by the forced oscillation technique (Raw-FOT) in groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…We studied this in three different strains of mice previously shown to have different degrees of responsiveness to methacholine. Other studies have shown the order of sensitivity to methacholine to be A/J > Balb/C > C57Bl/6 [25-27], with A/J often considered to be genetically hyperresponsive. We found that naïve mice of all of these strains were unaffected by either (RS)-, (S)- or (R)- albuterol treatment to a significant degree (Figures 4 and 5).…”
Section: Resultsmentioning
confidence: 99%
“…We studied this in three different strains of mice previously shown to have different degrees of responsiveness to methacholine. Other studies have shown the order of sensitivity to methacholine to be A/J > Balb/C > C57Bl/6 [25-27], with A/J often considered to be genetically hyperresponsive. We found that naïve mice of all of these strains were unaffected by either (RS)-, (S)- or (R)- albuterol treatment to a significant degree (Figures 4 and 5).…”
Section: Resultsmentioning
confidence: 99%
“…Airway Hyper-responsiveness-A dose-response curve to aerosolized methacholine (0, 10, 20, 40, 80, and 160 mg/ml in PBS) using two-chamber plethysmography (Buxco) in conscious mice was performed on the days indicated (20). Airway hyper-responsiveness was determined as specific airway resistance (sRaw) and compliance (sGaw) measured with each dose of methacholine and reported as the percent change from baseline.…”
Section: Cd4mentioning
confidence: 99%
“…Also, restrained DCP technique has been performed, because this technique is soundly based on the first principles of physics of the lung similar to invasive techniques and allows nonterminal measurements. It has recently been shown that there was an excellent correlation between sRaw-DCP method and airway resistance by the forced oscillation technique (19). These measurements were estimated on day 33 for all mice.…”
Section: Ahr Measurementmentioning
confidence: 99%